PHONOLOGICAL ERROR ANALYSIS OF MANDAILING TRIBE STUDENTS IN LEARNING ARABIC AT STATE ISLAMIC SCHOOL 4 MANDAILING NATAL - Muhammad Martua; Darwin Zainuddin (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
This study aims to analyze the phonological errors made by students at State Senior High School 4 Mandailing Natal in learning Arabic. This research employed a qualitative descriptive method. Data were collected through listening and recording techniques. Understanding Arabic phonology is very important to avoid mispronunciation of Arabic sounds. The results of this study revealed that the most frequent phonological errors made by students during reading activities occurred with the consonant sounds (dhāl, zāy, shīn, khā’, ẓā’). The main factor causing incorrect pronunciation of these consonant sounds is that students are not familiar with the articulation points of these sounds, and these consonants do not exist in the students’ mother tongue, making their pronunciation particularly challenging.